Fashion jewellery : catwalk and couture - Adams, Maia (London : Laurence King, 2010)
Displays contemporary catwalk and couture jewellery, profiling international fashion jewellers who combine traditional techniques and ultra-modern methods to create this new style of jewellery. Showcasing skilled craftsmanship, unusual materials and an often limited edition approach, this work harnesses the spirit of couture for the 21st century.## lexis Bittar -- Annabcn -- Arielle de Pinto -- Atelier 11 -- Bless -- Daisuke Sakaguchi -- David & Martin -- Delfina Delettrez -- Elke Kramer -- Erickson Beamon -- Florian -- Husam El Odeh -- Jordan Askill -- Judy Blame -- Lara Bohinc -- Laura B -- Ligia Dias -- Marion Vidal -- Michelle Jank -- Naomi Filmer -- Natalia Brilli -- Philip Crangi -- R -- Sabrina Dehoff -- Scott Stephen -- Scott Wilson -- Shaoo -- Sonia Boyajian -- Sonja Bischur -- Uli Raap -- Wouters & Hendrix -- Yazbukey -- Yoshinko Creatino Paris
boek